A review of traditional embroidery from China in relation to knowledge management and design - Xueqin Zhong (2019)
© 2019 IEEE. This paper presents findings from a review of the literature about traditional embroidery of China, knowledge management and design. It aims to identify knowledge domains, which are relevant to enabling the future viability of traditional embroidery. This paper introduces a significance of traditional embroidery to China, including its geographical indications (GIs), intangible cultural heritage (ICH) and Soft Power. It also identifies the four traditional embroideries that represent the intangible cultural heritage of China. The situation analysis of these four embroideries is discussed, resulting in the rationale for selecting Shu embroidery for in-depth case study. Next, it outlines the meaning of knowledge management and knowledge audit and the five secondary case-studies of knowledge management in relation to business and community development. This results in the identification of key factors of success (collaboration, the importance of leadership in integration, customer-oriented, design and implementation and networks of knowledge sharing). Furthermore, it outlines five secondary case-studies of design contributions in relation to knowledge audit and business development of crafts communities. This results in the identification of potential areas for design contributions, including: product design and development (i.e., pattern design); design for marketing and sales (i.e., branding); design in production development; and design for craft education (i.e., knowledge transfer and knowledge sharing). Design for sustainability, co-design and service-design are critical to the success of community development. The next step of this research is about knowledge audit, including developments of a conceptual model of critical knowledge domains for business and community development. Fieldwork will be conducted in craft communities that produce Shu embroidery in Sichuan, China in order to identify their existing knowledge and the missing knowledge (gaps in knowledge). It concludes with three main research questions generated to help guide the fieldwork.